Masak, Macak, Manak Nowadays through Challenge-Based Research on Nol Dance Creation - Yulela Nur Imama; Michiyo Yoneno Reyes (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Patriarchy in Javanese culture gives birth to gender stratification between women and men. This attitude has an impact on the work delegated to women. This stigma requires women to fulfill cultural values that include 3M, namely masak, macak, manak. This study aims to find out the existence and relevance of the values of masak, macak, and manak, in the form of dance works, and to find out how these values must be maintained. The method used is the method of creation based on the concept of art-based research. This research on the creation of dance works is based on challenges, namely through the process of creating challenges. The study was conducted by challenging ten participants to communicate and do several things intensely, both personally and communally, for seven days online through the